Distinct Cell Types With the Bitter Receptor Tas2r126 in Different Compartments of the Stomach - Widmayer, Patricia; Partsch, Vanessa; Pospiech, Jonas; Kusumakshi, Soumya; Boehm, Ulrich; Breer, Heinz (Frontiers in Physiology, 2020)
Cells expressing bitter taste receptors (T2Rs or Tas2rs) in extraoral tissues are considered to be chemosensory cells mediating protective responses to potentially harmful or even antiinflammatory or antimicrobial compounds. In a previous study the activity of the Tas2R143/Tas2R135/Tas2r126 cluster promoter in the stomach was monitored using a Cre-reporter mouse line. Reporter gene expression and Tas2r126 mRNA were found in brush cells located at the distal wall of the gastric groove. In this study, we explored whether brush cells and epithelial cells of the stomach in fact contain the Tas2r126 receptor protein. Using immunohistochemistry, we demonstrate the presence of Tas2r126 immunoreactivity in different cell populations in the glandular stomach, in a subset of brush cells at the gastric groove and in unique glandular units as well as in certain enteroendocrine cells. In brush cells at the gastric groove, a strong immunofluorescence signal for the Tas2r126 receptor was observed at the most apical region of the cells, i. e. the microvillar tuft. In addition, we found a high density of Tas2r126-positive brush cells in the unique glandular units. These invaginations are located distally to the groove, open directly into the furrow and are enwrapped by smoothelin-immunoreactive muscles. In the corpus, Tas2r126 immunoreactivity was found in histamine-producing enterochromaffin-like (ECL) cells and in ghrelin-producing X/A-like cells, the main enteroendcrine cells of this compartment. In the antrum, Tas2r126 labeling was observed in serotonin-storing enterochromaffin (EC) cells and ghrelin cells, both representing only minor populations of enteroendocrine cells in this compartment. In conclusion, our data provide evidence for the presence of the Tas2r126 receptor protein in distinct cell types in the epithelium lining the mouse stomach which render the stomach responsive to agonists for bitter receptors.